Defying strain in the synthesis of an electroactive bilayer helicene. Issue 4 (20th November 2018) - Milton, Margarita; Schuster, Nathaniel J.; Paley, Daniel W.; Hernández Sánchez, Raúl; Ng, Fay; Steigerwald, Michael L.; Nuckolls, Colin
Abstract : Visible-light-induced oxidative cyclization of a phenanthrene framework overcomes immense strain to yield a bilayer perylene-diimide helicene. Abstract : We report the synthesis of a bilayer chiral nanographene incorporating a [7]helicene scaffold and two perylene-diimide (PDI) subunits. Twofold visible-light-induced oxidative cyclization of a phenanthrene framework selects for the desired PDI-helicene, despite the immense strain that distinguishes this helicene from two other accessible isomers. This strain arises from the extensive intramolecular overlap of the PDI subunits, which precludes racemization, even at elevated temperatures. Relative to a smaller homologue, this PDI-helicene exhibits amplified electronic circular dichroism. It also readily and reversibly accepts four electrons electrochemically. Modifications to the core phenanthrene subunit change the fluorescence and electrochemistry of the PDI-helicene without significantly impacting its electronic circular dichroism or UV-visible absorbance.